A fish-parasitic isopod (Cymothoidae) on the pachyrhizodont Goulmimichthys roberti from the lower Turonian (Upper Cretaceous) Vallecillo plattenkalk, NE Mexico. (January 2022) - Stinnesbeck, Eva S.; Wägele, Johann W.; Herder, Fabian; Rust, Jes; Stinnesbeck, Wolfgang
Abstract: The platy limestone (plattenkalk) deposit of Vallecillo in northeastern Mexico is widely known for its well preserved and diverse fish and marine reptilian assemblage dated to the early–middle Turonian (Late Cretaceous). A single specimen of the pachyrhizodont G. roberti revealed the first Cretaceous isopod (Crustacea, Arthropoda) attached to a fish host. Preservation allows for the interpretation of the entire body and most appendages. A parasitic lifestyle of the isopod is inferred based on the specimen's morphology including claw-like dactyli, but is also inferred based on the anoxic bottom conditions variously interpreted for the Vallecillo plattenkalk deposit, which excluded scavengers. The individual is here referred to the family Cymothoidae and described as Mothocya vallecillae n. sp. Highlights: First Cretaceous record of a parasitic Isopod associated with the fish host. First Isopod record from Vallecillo. Claw-like dactyli allow being assigned to Cymothoidae. The Vallecillo individual is interpreted as a new species, Mothocya vallecillae.